ADVANCED DIRECTIVES: AN OVERVIEW - Hertlein, Melinda (Acta Scientiae et Intellectus, 2024)
Advanced directives are important for individuals to have documented their wishes when end of life decisions need to be made. Quality of life has a unique definition to each individual. Every individual has the right to their own belief and perspective of how they want to direct their health care. During medical emergencies, life sustaining measures are taken to preserve and maintain life. Many of times the outcomes do not result in the quality of life that the individual would want resulting in end of life discussions. This is why the importance of advanced directives should be a priority within our county to reduce the amount of unnecessary healthcare cost and burdens on family and friends.